Soil mesofauna promote mineral-associated organic matter formation under ambient and future climates - Gerrit Angst; Lisa Hinkelthein; Qun Liu; Alfred Lochner; Ondřej Mudrák; Travis Meador; Martin Schädler; Stefan Scheu; Marie Sünnemann; Rui Yin; Šárka Angst; Nico Eisenhauer (Agriculture, Ecosystems & Environment, 2026)

Sustainable Land Use Enhances Soil Microbial Respiration Responses to Experimental Heat Stress - Rémy Beugnon; Nico Eisenhauer; Alfred Lochner; Margarete J. Blechinger; Paula E. Buhr; Simone Cesarz; Monica A. Farfan; Olga Ferlian; Amanda J. Rompeltien Howard; Yuanyuan Huang; Blanca S. Kuhlmann; Nora Lienicke; et al. (Global Change Biology, 2025)
Soil microbial communities provide numerous ecosystem functions, such as nutrient cycling, decomposition, and carbon storage. However, global change, including land‐use and climate changes, affects soil microbial communities and activity. As extreme weather events (e.g., heatwaves) tend to increase in magnitude and frequency, we investigated the effects of heat stress on the activity (e.g., respiration) of soil microbial communities that had experienced four different long‐term land‐use intensity treatments (ranging from extensive grassland and intensive grassland to organic and conventional croplands) and two climate conditions (ambient vs. predicted future climate). We hypothesized that both intensive land use and future climate conditions would reduce soil microbial respiration (H1) and that experimental heat stress would increase microbial respiration (H2). However, this increase would be less pronounced in soils with a long‐term history of high‐intensity land use and future climate conditions (H3), and soils with a higher fungal‐to‐bacterial ratio would show a more moderate response to warming (H4). Our study showed that soil microbial respiration was reduced under high land‐use intensity (i.e., −43% between extensive grassland and conventional cropland) and future climate conditions (−12% in comparison to the ambient climate). Moreover, heat stress increased overall microbial respiration (+17% per 1°C increase), while increasing land‐use intensity reduced the strength of this response (−25% slope reduction). In addition, increasing soil microbial biomass and fungal‐to‐bacterial ratio under low‐intensity land use (i.e., extensive grassland) enhanced the microbial respiration response to heat stress. These findings show that intensive land use and climate change may compromise the activity of soil microbial communities as well as their respiration under heatwaves. In particular, soil microbial communities under high‐intensity land use and future climate are less able to respond to additional stress, such as heatwaves, potentially threatening the critical ecosystem functions driven by soil microbes and highlighting the benefits of more sustainable agricultural practices.

Sustainable Land Use Strengthens Microbial and Herbivore Controls in Soil Food Webs in Current and Future Climates - Marie Sünnemann; Andrew D. Barnes; Angelos Amyntas; Marcel Ciobanu; Malte Jochum; Alfred Lochner; Anton M. Potapov; Thomas Reitz; Benjamin Rosenbaum; Martin Schädler; Anja Zeuner; Nico Eisenhauer (Global Change Biology, 2024)
Climate change and land‐use intensification are threatening soil communities and ecosystem functions. Understanding the combined effects of climate change and land use is crucial for predicting future impacts on soil biodiversity and ecosystem functioning in agroecosystems. Here, we used a field experiment to quantify the combined effects of climate change (warming and altered precipitation patterns) and land use (agricultural type and management intensity) on soil food webs across nematodes, micro‐, and macroarthropods. Specifically, we investigated two types of agricultural systems—croplands and grasslands—under both high‐ and low‐intensity management. We focused on assessing the functioning of soil food webs by investigating changes in energy flux to consumers in the main trophic groups: decomposers, microbivores, herbivores, and predators. While the total energy flux and detritivory, herbivory and predation in the soil food web remained unchanged across treatments, low‐intensity land use—compared to high intensity—led to higher microbivory and microbial control under future climate conditions (i.e., warming and summer drought) in croplands and grasslands. At the same time, microbial and herbivore control were higher under low‐intensity land use in croplands and grasslands. Overall, our results underscore the potential benefits of less intensive, more sustainable management practices for soil food‐web functioning under current and future climate scenarios.

Large‐scale drivers of relationships between soil microbial properties and organic carbon across Europe - Linnea C. Smith; Alberto Orgiazzi; Nico Eisenhauer; Simone Cesarz; Alfred Lochner; Arwyn Jones; Felipe Bastida; Guillaume Patoine; Thomas Reitz; François Buscot; Matthias C. Rillig; Anna Heintz‐Buschart; et al. (Global Ecology and Biogeography, 2021)
Aim Quantify direct and indirect relationships between soil microbial community properties (potential basal respiration, microbial biomass) and abiotic factors (soil, climate) in three major land‐cover types. Location Europe. Time period 2018. Major taxa studied Microbial community (fungi and bacteria). Methods We collected 881 soil samples from across Europe in the framework of the Land Use/Land Cover Area Frame Survey (LUCAS). We measured potential soil basal respiration at 20 ºC and microbial biomass (substrate‐induced respiration) using an O 2 ‐microcompensation apparatus. Soil and climate data were obtained from the same LUCAS survey and online databases. Structural equation models (SEMs) were used to quantify relationships between variables, and equations extracted from SEMs were used to create predictive maps. Fatty acid methyl esters were measured in a subset of samples to distinguish fungal from bacterial biomass. Results Soil microbial properties in croplands were more heavily affected by climate variables than those in forests. Potential soil basal respiration and microbial biomass were correlated in forests but decoupled in grasslands and croplands, where microbial biomass depended on soil carbon. Forests had a higher ratio of fungi to bacteria than grasslands or croplands. Main conclusions Soil microbial communities in grasslands and croplands are likely carbon‐limited in comparison with those in forests, and forests have a higher dominance of fungi indicating differences in microbial community composition. Notably, the often already‐degraded soils of croplands could be more vulnerable to climate change than more natural soils. The provided maps show potentially vulnerable areas that should be explicitly accounted for in future management plans to protect soil carbon and slow the increasing vulnerability of European soils to climate change.